Cyclo‐Dipnictadialanes. Issue 45 (5th October 2021) - Nees, Samuel; Fantuzzi, Felipe; Wellnitz, Tim; Fischer, Malte; Siewert, Jan‐Erik; Goettel, James T.; Hofmann, Alexander; Härterich, Marcel; Braunschweig, Holger; Hering‐Junghans, Christian
Abstract: Using the Al I precursor Cp 3t Al in conjunction with triphosphiranes (PAr)3 (Ar=Mes, Dip, Tip) we have succeeded in preparing Lewis base‐free cyclic diphosphadialanes with both the Al and P atoms bearing three substituents. Using the sterically more demanding Dip and Tip substituents the first 1, 2‐diphospha‐3, 4‐dialuminacyclobutanes were obtained, whereas with Mes substituents [Cp 3t Al(μ‐PMes)]2 is formed. This divergent reactivity was corroborated by DFT studies, which indicated the thermodynamic preference for the 1, 2‐diphospha‐3, 4‐dialuminacyclobutane form for sterically more demanding groups on phosphorus. Using Cp*Al we could extend this concept to the corresponding cyclic diarsadialanes [Cp*Al(μ‐AsAr)]2 (Ar=Dip, Tip) and additionally add the phosphorus variants [Cp*Al(μ‐PAr)]2 (P=Mes, Dip, Tip). The reactivity of one variant [Cp 3t Al(μ‐PPh)]2 towards NHCs was tested and resulted in double NHC‐stabilised [Cp 3t (IiPr2 )Al(μ‐PPh)]2 . Abstract : Pnictaalenes with a pnictogen−aluminium double bond are inherently unstable and prone to dimerization. The synthesis of Lewis‐base‐free dipnictadialenes is revealed. It is shown that depending on the steric profile of the substituents either the alternating [Cp x Al(μ‐PAr)]2 dimers or the head‐to‐head species [ArPnAlCp 3t ]2 are formed. DFT studies corroborate that the different outcomes are thermodynamically driven.